The architecture of digital imaging (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2019)
What is image? Around the concept of image there has been speculation that man used one image to refer to another, from the very birth of language. The image has dematerialized, transcoded, discretized, datified, codified, and floods all spaces: real and virtual. It is necessary to understand the architecture of the image, not only to represent but also for its permanence.
Keywords: Image; Code image; Format; Data; Metadata; Preservation; Transcodification; Presentation